Language learning from children at an early age - Dulaj, Fridrik (Technium Social Sciences Journal, 2023)
Language as an essential factor in human life can be said to be born together with the human. But how does it develop further and how is it acquired by the individual? The issues that will be treated in this paper belong to the psycholinguistic field, a research discipline which is really in the first steps of its development, but considering that without acquisition, language cannot be realized and that its acquisition starts from birth, it turns out to be an interesting issue to be treated. The human with a sound mental and social mechanism acquires language from birth, the first stages of childhood to the age that is considered as the age of almost complete acquisition of language and onwards. In this paper, as well, we will address the topic of speech acquisition by children, who initially use and speak the language as they hear it without their full consciousness, and later to influence to an older age and conscious way in it, by giving it a broader semantic meaning. Regarding the acquisition of speech by children, there are a number of factors that significantly affect children and their speech, from the family, institutional and social background, etc. Therefore, our paper aims to clarify some important issues about language acquisition by children.